EFEKTIVITAS SANKSI EKONOMI UNI EROPA TERHADAP RUSIA DALAM KASUS ANEKSASI KRIMEA - Siregar, Dewi Mentari; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aim to explain the effectiveness of European Union economic sanction against Russia through the annexation of Crimean Peninsula by Russia. Crimea is a major land mass on the Northern Coast of the black Sea. On March 2014, Crimean separatist group make a voting and the result shows most of voters want to join the Russian State. This action was followed soon by Russia’s annexation. Russia have been violated many international agreements and bring it to the condemnation by international community. European Union as a regional organization imposed economic sanctions against Russia.This case will be analyzed in international system level within liberalism paradigm and interdependence theory. System Level Analysis gave general pattern about the nation behavior and inter-nation interdependency while liberalism assumes that trade relation will create a good relation on international relation.Opposite with the relation between European Union and Russia nowadays. European Union and Russia have interdependence on trade relation before the crisis. Economic sanctions that imposed by European Union against Russia doesn’t work. Economic sanctions also inflict European Union as sanction’s giver. Russia kept holding Crimea as its territory because of its own interest on Crimea.Keywords : annexation, economic sanction, interdependency